STUDI EVALUASI PELAKSANAAN DAN KELEMBAGAAN PELAKSANA PROGRAM BENGKULU REGIONAL DEVELOPMENT PROJECT (BRDP) - Nusril, Nusril; Romdhon, M. Mustopa; Cahyadinata, Indra (Jurnal AGRISEP, 2005)
This research aims to explores level of success, constraints and benefits of BRDP on rural poor  community. Qualitative methods which were based on prepare data or information as parts of flexible methods was used. The results showed  that BRDPs implemetation has runned well. These was indicated by indicated the readiness and completed, range from province to village levels as well in infrastructure and institutional and beneficiaries. The success of implemented on village level instutitonal was supported by UPKD as leader on productive economic activities .These have UPKDs completed administration equipments, and the service product had competitive advantages comparing to others service product. The continuity  of the activities post project could be well quarantee since these problems both normative and outcome real aspects were minimized. This induces improving on net working systems among UPKD, completing the financial-budget systems based on norms, and optimalities of Financial Assistant roles in village.